Préteritum a kondicionál polského typu v kašubštině a v ruténštině - Knoll, Vladislav (Slavia Occidentalis, 2022)
Kashubian and Ruthenian (and Galician Ukrainian) have been developing under a strong Polish impact. In the article, I examine the occurrence of the past tense and conditional mood, modelled by Polish (of type chciałem, chciałbym) in texts and grammars of Ruthenian, Galician Ukrainian, Rusyn and Kashubian. While in case of the East Slavic languages, I present just an overview of the issue, I discuss more in-depth the grammatical evaluation and use of such forms in Kashubian from the oldest texts until current written usage. This shows the fact that the recommendations of Kashubian grammarians and the real written usage do not match. By comparing Kashubian with East Slavic written varieties under Polish influence, I intended to show that these languages have faced the same tendencies in dealing with the existence of grammar forms enforced by the Polish language, partly supported by certain dialects.